2021
DOI: 10.1093/ibd/izab193
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Necrosis Factor-like Ligand 1A Therapy Targets Tissue Inflammation and Fibrosis Pathways and Reduces Gut Pathobionts in Ulcerative Colitis

Abstract: Background The first-in-class treatment PF-06480605 targets the tumor necrosis factor-like ligand 1A (TL1A) molecule in humans. Results from the phase 2a TUSCANY trial highlighted the safety and efficacy of PF-06480605 in ulcerative colitis. Preclinical and in vitro models have identified a role for TL1A in both innate and adaptive immune responses, but the mechanisms underlying the efficacy of anti-TL1A treatment in inflammatory bowel disease (IBD) are not known. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…We found that the IBD-associated pathogen H. parainfluenzae [ 46 ] had a relatively higher abundance in the IBD patients compared to the non-IBD symptomatic patients. Schirmer et al found in their study of pediatric UC patients that H. parainfluenzae constituted one of the most significant changes in abundance linked to disease severity [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the IBD-associated pathogen H. parainfluenzae [ 46 ] had a relatively higher abundance in the IBD patients compared to the non-IBD symptomatic patients. Schirmer et al found in their study of pediatric UC patients that H. parainfluenzae constituted one of the most significant changes in abundance linked to disease severity [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the tumor necrosis factor family, TL1A plays a crucial role in apoptosis and T cell activation. It has been found to act importantly in inflammatory bowel disease, neuroimmunity, and neuroinflammation 10 . Besides, TL1A can mediate the activation of downstream signals like NLRP3 through TNFRs 11 .…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 56 One of the hallmarks of UC in our study was the expansion of H. parainfluenzae , which has been associated with increased level of acylcarnitine in IBD. 57 Expansion of H. parainfluenzae was found in pediatric UC patients, 32 , 38 , 58 and its reduction in colonic biopsies of adult UC patients in response to novel anti-TNF neutralizing antibody has been reported, 59 suggesting a potential role of H. parainfluenzae in IBD pathogenesis. The enrichment of Haemophilus in biopsies of CD patients was reported in the pediatric treatment-naïve cohorts, 27 , 60 but we did not observe a similar trend.…”
Section: Discussionmentioning
confidence: 97%